Value chains for nutrition - Hawkes, Corinna; Ruel, Marie T. (International Food Policy Research Institute, 2011)
Value-chain approaches are already used as development strategies to enhance the livelihoods of food producers, but they have, to date, rarely been used explicitly as a tool to achieve nutritional goals, and they have not been sensitive to nutritional concerns. This brief seeks to identify if, why, and how value-chain concepts could and should be applied to enhance the ability of agriculture to improve nutrition.